2019
DOI: 10.1177/0886260519872978
|View full text |Cite
|
Sign up to set email alerts
|

Tipping the Scales: Effects of Gender, Rape Myth Acceptance, and Anti-Fat Attitudes on Judgments of Sexual Coercion Scenarios

Abstract: A damaging belief exists that to become a victim of sexual violence, victims must be deemed sexually desirable. As a result, sexual violations where the victims are individuals whom society may deem as less attractive—such as overweight women—may elicit less empathy for the victim or minimize the likelihood they are believed. Yet, there is some evidence that overweight women actually report higher rates of sexual violence than women of other weight categories. Although there has been some research implicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 57 publications
5
31
0
Order By: Relevance
“…It is plausible that greater emphasis on weight through the employment of visual images or greater discussion of the survivor's size would have yielded the hypothesized effect. Indeed, research has generally shown that greater weight bias is associated with lower perpetrator blame and higher survivor blame (Clarke & Lawson, 2009;Clarke & Stermac, 2011;Zidenberg et al, 2021), findings further supported in this investigation.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It is plausible that greater emphasis on weight through the employment of visual images or greater discussion of the survivor's size would have yielded the hypothesized effect. Indeed, research has generally shown that greater weight bias is associated with lower perpetrator blame and higher survivor blame (Clarke & Lawson, 2009;Clarke & Stermac, 2011;Zidenberg et al, 2021), findings further supported in this investigation.…”
Section: Discussionsupporting
confidence: 83%
“…Generally speaking, greater weight bias (WB) has been associated with more favorable attitudes toward the perpetrator and less favorable attitudes toward the survivor of a sexual assault (Clarke & Lawson, 2009; Clarke & Stermac, 2011; Zidenberg et al, 2021), particularly among study participants who are men (Gotovac & Towson, 2015). Weight bias, also termed weight stigma, refers to the discriminatory acts and negative ideologies targeted toward individuals because of their weight and size.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In one of our studies (Goh et al, 2022, Study C1), participants assigned less severe punishments to perpetrators who harassed nonprototypical women than to those who harassed prototypical women. Similarly, other researchers have found that perpetrators who sexually assault overweight (vs. not overweight) and Black (vs. White) women are perceived as less deserving of punishment (Foley et al, 1995;Zidenberg et al, 2021). Additionally, Black, compared with White, assault victims are more likely to receive substandard care, discriminatory treatment, and secondary revictimization from medical practitioners and police officers (Coker at al., 2015;Jacques-Tiura et al, 2010).…”
Section: Consequences Of Perceptions Of Sexual Harassmentmentioning
confidence: 88%
“…Additionally, Zidenberg et al (2021) and Barnett et al (2018) both carried out studies in which men were more likely to accept rape stereotypes than women, while other factors additionally had an effect, such as religiosity, anti-fatness, and sympathy for victims. It will be useful to gain a similar understanding of gender and rape stereotype acceptance in the UK.…”
Section: Introductionmentioning
confidence: 99%